Direct and converse magnetoelectric effect at resonant frequency in laminar piezoelectric-magnetostrictive composite. - Popov, C.; Chang, Harrison Hoon Seok; Record, P. M.; Abraham, E.; Whatmore, Roger W.; Huang, Zhaorong (Springer Science Business Media, 2008)
Laminar piezoelectric-magnetostrictive composites using piezoelectric lead zirconate titanate ceramics and the giant magnetostrictive rare-earth-iron alloy Terfenol-D were prepared by epoxy bonding. The direct and converse magnetoelectric (ME) effects at and off the mechanical resonant frequency were characterized and compared to the theoretical modelling. The mechanical resonant frequency of the composites depended on the sample orientation and the magnetic DC bias field. In the longitudinal configuration, the resonant frequency shifted down monotonically with the increasing bias field. When the sample was in the transverse configuration, the resonant frequency decreased with the increasing field at first. However, at higher bias, it shifted up with the increasing bias. A phenomenological model based on the Ã Â E effect of magnetostrictive materials is proposed to explain the observed phenomena
Keywords: Magnetoelectric effect; Piezoelectric; Magnetostrictive; PZT; ΔE effect; Orientation dependence